Vascular access site management during electrophysiology procedures: a European Heart Rhythm Association survey - Mills, Mark; Gupta, Dhiraj; Luther, Vishal; Zylla, Maura Magdalena; Futyma, Piotr; Perrotta, Laura; Mazurek, Michal; Heeger, Christian-Hendrick; Marcantoni, Lina; Metzner, Andreas; Chun, Julian K R (Europace, 2025)
Reliable vascular access and haemostasis techniques are important to the safety of electrophysiology (EP) procedures. This European Heart Rhythm Association (EHRA) survey aimed to evaluate contemporary vascular access site management practices across international EP centres.A 30-question survey was disseminated via the EHRA between March and April 2025, with 401 responses from professionals across 51 countries. Most respondents were cardiology consultants/attendings (82.0%), with 57.3% performing over 150 EP procedures annually. Ultrasound guidance for vascular access was usually or always used by 71.7%, though 21.4% used it rarely or never, and only 17.3% had received formal ultrasound training. Institutional protocols for haemostasis were lacking in around half (46.8%) of centres. Suture-mediated closure was the most common method for haemostasis (60.4%), followed by manual compression (33.0%) and vascular closure devices (VCDs, 5.8%). The figure-of-eight suture with a hand-tied knot was the most frequently used suture technique (79.7%). Just over a third (36.0%) had experience with VCDs, typically reserved for high-risk cases. For procedures requiring transeptal access, 38.1% administered heparin before transeptal puncture, while protamine was rarely or never used by 62.1%. Anticoagulation was partially interrupted in 52.1% and continued uninterrupted in 41.1% of routine atrial fibrillation (AF) ablations. The median bed rest duration post-procedure ranged from 4 h (right-sided EP procedures) to 6 h (AF or left-sided EP procedures). The average quoted vascular complication risk during consent was 3% (inter-quartile range 1-5%).This survey highlights marked variation in vascular access site management during and following EP procedures, emphasizing the need for further clinical trials to inform best practice and guide future standardization efforts.